Relationship Between Digital Creativity, Parenting Style, and Adolescent Performance - Pérez-Fuentes, María del Carmen; Molero Jurado, María del Mar; Oropesa Ruiz, Nieves Fátima; Simón Márquez, María del Mar; Gázquez Linares, José Jesús (Frontiers in Psychology, 2019)
Introduction: Today’s adolescents live immersed in the digital world, and are more and more familiarized with the use of electronic devices. At the same time, the new technologies have become established as a powerful resource in teaching and learning, providing new texts where the limits of time and space are overcome. Digital creativity is part of people’s daily lives and must be developed from the school and family context. Objective: The objective of this study was to analyze the relationship between digital creativity, parenting style and academic performance. Method: This analysis was carried out in a sample of 742 adolescents in Middle School and High School aged 13 to 19. Digital creativity was evaluated using the Creative Behavior Questionnaire: Digital (CBQD). The Parenting Style Scale was used to evaluate the perception teenage boys and girls have of the various dimensions of their parents’ educational style. Results: Parenting styles were established as a mediating variable in the relationship between digital creativity and academic performance. Conclusion: The preponderant role of digital creativity is emphasized as a facilitating tool for teaching, as well as significant learning in the classrooms, and the role of parenting styles in academic performance for improving the relationship between family and school.